2013
DOI: 10.4314/ejesm.v6i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mancozeb-treated lettuce (<i>Lactuca sativa</i>) on wistar rat liver

Abstract: Vegetable contamination by pesticides presents current problem of public health. Previous studies have shown that 60% vegetables sampled collected in Lomé (Togo) have pesticide residues exceeding the tolerable limits. Because mancozeb, ethylene bis-dithiocarbamate, is mainly used, more than five times, during the growth of lettuce (Lactuca sativa), the aim of the present investigation is to evaluate the potential effect of mancozeb-treated lettuce on the rat liver physiology. Mancozeb-treated lettuce and two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In sub acute group, significant (p≤0.05) increase in bilirubin levels in ziram intoxicated birds was oberved at day 20 of intoxication and in subchronic group from 10 day onwards when compared to the control. These finding could be correlated to reports of Adjrah et al (2013) who reported increase in the bilirubin levels of wister rats after exposure to mancozeb carbamate. The increase in the bilirubin level after the exposure to zineb carbamate in rats has also been reported by Mountie et al (1983).…”
Section: Liver Function Test (Lft)supporting
confidence: 89%
“…In sub acute group, significant (p≤0.05) increase in bilirubin levels in ziram intoxicated birds was oberved at day 20 of intoxication and in subchronic group from 10 day onwards when compared to the control. These finding could be correlated to reports of Adjrah et al (2013) who reported increase in the bilirubin levels of wister rats after exposure to mancozeb carbamate. The increase in the bilirubin level after the exposure to zineb carbamate in rats has also been reported by Mountie et al (1983).…”
Section: Liver Function Test (Lft)supporting
confidence: 89%
“…A study on the consumption of mancozeb-treated vegetables and their effects on rat livers verified that mancozeb contributes to the occurrence of liver disease 39 . Ksheerasagar and Kaliwal 40 observed that the weight of liver and protein quantity were decreased when mice were exposed daily to mancozeb for 30 days.…”
Section: Discussionmentioning
confidence: 87%
“…Fungicides induced a significant decrease in the serum antioxidant enzymes activities, superoxide dismutase and increase in lipid peroxidation in albino rats [27,46]. Marked reduction in antioxidant enzymes activities and tissue glutathione contents resulted in oxidative damage of tissues and leads to apoptosis in cellular systems, especially hepatocytes [7,47].…”
Section: Discussionmentioning
confidence: 99%